Trigonometric Ratios of Multiple Angles | kullabs.com

## Note on Trigonometric Ratios of Multiple Angles

• Note
• Things to remember
• Videos
• Exercise
• Quiz

Example for Trigonometric ratios of Multiple Angles

If A is an angle, then 2A, 3A, 4A, 5A, etc. are called multiple angles of A. In this section we will discuss about the trigonometric ratios of angles 2A and 3A in terms of A.

(a) sin2A = sin(A + A) = sinA. cosA + cosA. sinA = 2sinA. cosA

(b) sin2A = 2sinA. cosA = $$\frac{2sinA. cosA}{1}$$ =$$\frac{2sinA. cosA}{cos^{2}A + sin^{2}A}$$ =$$\frac{\frac{2sinA. cosA}{cos^2A}}{\frac{cos^2A}{cos^2A} + \frac{sin^2A}{cos^2A}}$$ = $$\frac{2tanA}{1 + tan^2A}$$

(c) sin2A =$$\frac{2tanA}{1 + tan^2 A}$$ =$$\frac{\frac{2}{cotA}}{1 +\frac{1}{cot^2 A}}$$ =$$\frac{2}{cotA}$$x$$\frac{cot^2A}{1 + cot^2 A}$$ =$$\frac{2cotA}{1 + cot^2 A}$$

(d) cos2A = cos(A + A) = cosA. cosA - sinA. sinA = cos2A - sin2A

(e) cos2A = cos2A - sin2A = 1 - sin2A - sin2A = 1 - 2sin2A

(f) cos2A = cos2A - sin2A = cos2A - (1 - cos2A) = 2cos2A - 1

(g) cos2A = cos2A - sin2A =$$\frac{cos^2A - sin^2A}{1}$$ =$$\frac{cos^2A - sin^2A}{cos^2A + sin^2A}$$ =$$\frac{\frac{cos^2A}{cos^2A} - \frac{sin^2A}{cos^2A}}{\frac{cos^2A}{cos^2A} + \frac{sin^2A}{cos^2A}}$$ =$$\frac{1 - tan^2A}{1 + tan^2A}$$

(h) cos2A =$$\frac{1 - tan^2A}{1 + tan^2A}$$ =$$\frac{1 - \frac{1}{cot^2A}}{1 +\frac{1}{cot^2A}}$$ =$$\frac{cot^2A - 1}{cot^2A + 1}$$

(i) tan2A = tan(A + B) =$$\frac{tanA + tanA}{1 - tanA. tanA}$$ =$$\frac{2tanA}{1 - tan^2A}$$

(j) tan2A =$$\frac{2tanA}{1 - tan^2A}$$ =$$\frac{\frac{2}{cotA}}{1 -\frac{1}{cot^2A}}$$ =$$\frac{2}{cotA}$$ x $$\frac{cot^2A}{cot^2A - 1}$$

(k) cot2A = cot (A + A) =$$\frac{cotA. cotA - 1}{cotA + cotA}$$ =$$\frac{cot^2A - 1}{2cotA}$$

(l) cot2A =$$\frac{cot^2A - 1}{2cotA}$$ =$$\frac{\frac{1}{tan^2A} - 1}{\frac{2}{tanA}}$$ =$$\frac{1 - tan^2A}{tan^2A}$$ x $$\frac{1 - tan^2 A}{2 tanA}$$ =$$\frac{1 - tan^2 A}{2 tanA}$$

Some useful results

(a) 1 + cos2A = 1 + cos2A - sin2A = 1 - sin2A + cos2A = cos2A + cos2A = 2cos2A

(b) 1 - cos2A = 1 - (cos2A - sin2A) = 1 - cos2A + sin2A = sin2A + sin2A = 2sin2A

(c) 1 + sin2A = cos2A + sin2A + 2 sinA .cosA = cos2A + 2 cosA . sinA + sin2A = (cosA + sinA)2

(d) 1 - sin2A = cos2A + sin2A - 2sinA .cosA = cos2A - 2 cosA .sinA + sin2A = (cosA - sinA)2

Trigonometric ratios of 3A in terms of A

(a) sin3A

= sin(2A + A)

= sin2A. cosA + cos2A. sinA

= 2 sinA . cosA. cosA + (1 - 2sin2A). sinA

= 2 sinA (1 - sin2A) + sinA - 2sin$$^3$$A

= 2sinA. 2sin$$^3$$A + sinA - 2 sin$$^3$$A

= 3 sinA - 4 sin$$^3$$A

(b) cos3A

= cos (2a + A)

= cos2A. cosA - sin2A. sinA

= (2cos2A - 1) cosA - 2sinA. cosA. sinA

= 2cos$$^3$$A - cosA - 2cosA (1 - cos2A)

= 2 cos$$^3$$A - cosA - 2cosA + 2cos$$^3$$A

= 4 cos$$^3$$A - 3 cosA.

(c) tan3A

= tan( 2A + A)

=$$\frac{tan2A + tanA}{1 - tan2A. tanA}$$

=$$\frac{\frac{2 tan A}{1 - tan^2 A} + tanA}{1 -\frac{2tan A}{1 - tan^2 A}. tanA}$$

=$$\frac{2 tan A + tan A - tan^3 A}{1 - tan^2 A - 2 tan^2 A}$$

=$$\frac{3 tan A - tan^3 A}{1 - 3 tan^2 A}$$

Geometrical proof of 2A formulae :

Let, O be the centre of the circle ABC and AB be a diameter. Let ∠CAB = A.

Then, ∠COB = 2A

Here, ∠ACB = 900. Let CM is perpendicular to AB.

Then, ∠ACM = 900 - A and hence. ∠BCM = A.

Now,

sin2A =$$\frac{CM}{OC}$$

=$$\frac{2CM}{2OC}$$

=$$\frac{2CM}{AB}$$

= 2 $$\frac{CM}{AC}$$. $$\frac{AC}{AB}$$

= 2sinA. cosA

And,

cos2A =$$\frac{OM}{OC}$$

=$$\frac{2OM}{2OC}$$

=$$\frac{2OM}{AB}$$

= $$\frac{(AO + OM) - (AO - OM)}{AB}$$

=$$\frac{AM - BM}{AB}$$

= $$\frac{AM}{AB}$$ - $$\frac{BM}{AB}$$

= $$\frac{AM}{AC}$$. $$\frac{AC}{AB}$$ - $$\frac{BM}{BC}$$. $$\frac{BC}{AB}$$

= cosA. cosA - sinA. sinA

= cos2A - sin2A

Again,

tan2A = $$\frac{CM}{OM}$$

= $$\frac{2CM}{2OM}$$

=$$\frac{2CM}{(AO + OM) - (AO -OM)}$$

= $$\frac{2CM}{(AO + OM) - (BO - OM)}$$

=$$\frac{2CM}{AM - BM}$$

=$$\frac{\frac{2CM}{AM}}{\frac{AM}{AM} - \frac{BM}{AM}}$$

=$$\frac{\frac{2CM}{AM}}{1 -\frac{BM}{CM}× \frac{CM}{AM}}$$

=$$\frac{2 tan A}{1 - tan A. tan A}$$

=$$\frac{2 tan A}{1 - tan^2 A}$$

 Multiple angles formulae sin2A = 2sinA. cosA tan2A =$$\frac{2cot A}{cot^2 A - 1}$$ sin2A =$$\frac{2tan A}{1 + tan^2 A}$$ cot2A =$$\frac{cot^2 A - 1}{2cot A}$$ sin2A =$$\frac{2cot A}{1 + cot^2 A}$$ cot2A =$$\frac{1 - tan^2 A}{2tan A}$$ cos2A = cos2A - sin2A 1 + cos2A = 2cos2A cos2A = 1 - 2sin2A 1 - cos2A = 2 sin2A cos2A = 2cos2A - 1 1 + sin2A = (cosA + sinA)2 cos2A =$$\frac{1 - tan^2 A}{1 + ttan^2 A}$$ 1 - sin2A = (cosA - sinA)2 cos2A =$$\frac{cot^2 A - 1}{cot^2 A + 1}$$ sin3A = 3 sinA - 4 sin $$^3$$ A tan2A =$$\frac{2 tan A}{1 - tan^2 A}$$ cos3A = 4 cos$$^3$$A - 3cos A tan3 A =$$\frac{3 tan A - tan^3 A}{1 - 3tan^2 A}$$

 sin2A = 2sinA. cosA tan2A =$$\frac{2cot A}{cot^2 A - 1}$$ sin2A =$$\frac{2tan A}{1 + tan^2 A}$$ cot2A =$$\frac{cot^2 A - 1}{2cot A}$$ sin2A =$$\frac{2cot A}{1 + cot^2 A}$$ cot2A =$$\frac{1 - tan^2 A}{2tan A}$$ cos2A = cos2A - sin2A 1 + cos2A = 2cos2A cos2A = 1 - 2sin2A 1 - cos2A = 2 sin2A cos2A = 2cos2A - 1 1 + sin2A = (cosA + sinA)2 cos2A =$$\frac{1 - tan^2 A}{1 + ttan^2 A}$$ 1 - sin2A = (cosA - sinA)2 cos2A =$$\frac{cot^2 A - 1}{cot^2 A + 1}$$ sin3A = 3 sinA - 4 sin $$^3$$ A tan2A =$$\frac{2 tan A}{1 - tan^2 A}$$ cos3A = 4 cos$$^3$$A - 3cos A tan3 A =$$\frac{3 tan A - tan^3 A}{1 - 3tan^2 A}$$

.

### Very Short Questions

L.H.S.

=$$\frac {sin\theta + sin2\theta}{1 + cos\theta + cos2\theta}$$

= $$\frac {sin\theta + 2sin\theta cos\theta}{1 + cos\theta + 2cos^2\theta - 1}$$

= $$\frac {sin\theta (1 + 2cos\theta)}{cos\theta (1 + 2cos\theta)}$$

= $$\frac {sin\theta}{cos\theta}$$

= tan$$\theta$$

Hence, L.H.S. = R.H.S. proved

Here,

sin3A cos2A

= (3 sinA - 4 sin3A) (1 - sin2A)

= 3 sinA - 4 sin3A - 3 sin3A + 4 sin5A

= 4 sin5A - 7 sin3A + 3 sinA Ans

Here,

L.H.S.

= cos 2A

= $$\frac {cos^2A - sin^2A}{1}$$

= $$\frac {cos^2A - sin^2A}{cos^2A + sin^2A}$$

=$$\frac {{\frac {cos^2A}{sin^2A}} - {\frac {sin^2A}{cos^2A}}}{{\frac {cos^2A}{cos^2A}} + {\frac {sin^2A}{cos^2A}}}$$

= $$\frac {1 - tan^2A}{1 + tan^2A}$$

Hence, L.H.S. = R.H.S. Proved

Here,

tan A = $$\frac 34$$

sin 2A

= $$\frac {2tan A}{1 + tan^2A}$$

= $$\frac {2 × \frac 34}{1 + (\frac {3}{4})^2}$$

= $$\frac {\frac 32}{1 + \frac {9}{16}}$$

= $$\frac 32$$× $$\frac {16}{25}$$

= $$\frac {24}{25}$$ Ans

cos 2A

= $$\frac {1 - tan^2A}{1 + tan^2A}$$

= $$\frac{1 -(\frac {3}{4})^2}{1 + (\frac {3}{4})^2}$$

= $$\frac {1 - \frac 9{16}}{1 +\frac 9{16}}$$

= $$\frac {\frac {16 - 9}{16}}{\frac {16 + 9}{16}}$$

= $$\frac {7}{16}$$× $$\frac {16}{25}$$

= $$\frac 7{25}$$ Ans

L.H.S.

=$$\frac {sin 2A}{1 + cos 2A}$$

= $$\frac {2 sin A cos A}{2 cos^2A}$$

= $$\frac {sin A}{cos A}$$

= tan A

Hence, L.H.S. = R.H.S. Proved

Here,

cos$$\alpha$$ = $$\frac {\sqrt 3}{2}$$

sin$$\alpha$$

= $$\sqrt {1 - cos^2\alpha}$$

= $$\sqrt {1 - (\frac {\sqrt 3}{2})^2}$$

=$$\sqrt {1 - \frac 34}$$

=$$\sqrt {\frac {4 - 3}{4}}$$

=$$\sqrt {\frac 14}$$

= $$\frac 12$$

sin3$$\alpha$$

= 3 sin$$\alpha$$ - 4 sin3$$\alpha$$

= 3× $$\frac 12$$ - 4× ($$\frac 12$$)3

= $$\frac 32$$ - $$\frac 48$$

= $$\frac 32$$ - $$\frac 12$$

= $$\frac {3 - 1}{2}$$

= $$\frac 22$$

= 1 Ans

Again,

cos 3$$\alpha$$

= 4 cos2$$\alpha$$ - 3 cos$$\alpha$$

= 4 ($$\frac {\sqrt 3}{2}$$)3- 3× $$\frac {\sqrt 3}{2}$$

= $$\frac {12\sqrt 3}{8}$$ - $$\frac {3\sqrt 3}{2}$$

= $$\frac {3\sqrt 3}{2}$$ - $$\frac {3\sqrt 3}{2}$$

= 0 Ans

L.H.S.

=4 (cos310° + sin320°)

=4cos310° + 4sin320°

= [cos 3(10°) + 3 cos 10°] + [3 sin20° - sin 3(20°)]

= cos 30° + 3 cos 10° + 3 sin 20° - sin 60°

= $$\frac {\sqrt 3}{2}$$ + 3 (cos 10° + sin 20°) - $$\frac {\sqrt 3}{2}$$

=3 (cos 10° + sin 20°)

Hence, L.H.S. = R.H.S. Proved

Here,

cos$$\theta$$ = $$\frac {12}{13}$$ and sin$$\alpha$$ = $$\frac 45$$

sin$$\theta$$

= $$\sqrt {1 - cos^2\theta}$$

= $$\sqrt {1 - (\frac {12}{13})^2}$$

= $$\sqrt {\frac {169 - 144}{169}}$$

= $$\sqrt {\frac {25}{169}}$$

= $$\frac 5{13}$$

cos$$\alpha$$

= $$\sqrt {1 - sin^2\alpha}$$

= $$\sqrt {1 - (\frac {4}{5})^2}$$

= $$\sqrt {\frac {25 - 16}{25}}$$

= $$\sqrt {\frac 9{25}}$$

= $$\frac 35$$

∴ sin 2$$\theta$$ = 2 sin$$\theta$$ cos$$\theta$$ = 2× $$\frac 5{13}$$× $$\frac {12}{13}$$ = $$\frac {120}{169}$$ Ans

∴ cos 2$$\alpha$$ = 2 cos2$$\alpha$$ - 1 = 2× $$\frac 35$$× $$\frac 35$$ - 1 = $$\frac {18 - 25}{25}$$ = -$$\frac 7{25}$$ Ans

Here,

3$$\theta$$ + $$\theta$$ = 4$$\theta$$

Putting tan on both,

tan (3$$\theta$$ + $$\theta$$) = tan 4$$\theta$$

or, $$\frac {tan 3\theta + tan\theta}{1 - tan 3\theta tan\theta}$$ = tan 4$$\theta$$

or, tan 3$$\theta$$ + tan$$\theta$$ = tan 4$$\theta$$ - tan$$\theta$$ tan 3$$\theta$$ tan 4$$\theta$$

or,tan$$\theta$$ tan 3$$\theta$$ tan 4$$\theta$$ =tan 4$$\theta$$ -tan 3$$\theta$$ -tan$$\theta$$

Hence, L.H.S. = R.H.S. proved

L.H.S.

=$$\frac {sin 5\theta}{sin \theta}$$ - $$\frac {cos 5\theta}{cos \theta}$$

= $$\frac {sin 5\theta cos \theta - cos 5\theta sin \theta}{sin \theta cos \theta}$$

= $$\frac {sin (5\theta - \theta)}{sin\theta cos\theta}$$

= $$\frac {sin 4\theta}{sin\theta cos\theta}$$

= $$\frac {sin 2(2\theta)}{sin\theta cos\theta}$$

= $$\frac {2 sin 2\theta cos 2\theta}{sin\theta cos\theta}$$

= $$\frac {2 × 2 sin\theta cos\theta cos2\theta}{sin\theta cos\theta}$$

= 4 cos 2$$\theta$$

Hence, L.H.S. = R.H.S. Proved

L.H.S.

= $$\frac {cos^3A + sin^3A}{cosA + sinA}$$

= $$\frac {(cosA + sinA)(cos^2A + sin^2A - sinA cosA)}{cosA + sinA}$$

= 1 - $$\frac {2 sinA cosA}{2}$$

= 1 - $$\frac 12$$sin 2A

Hence, L.H.S. = R.H.S. Proved

L.H.S.

=$$\frac 1{tan3A - tanA}$$ - $$\frac 1{cot3A - cotA}$$

=$$\frac 1{tan3A - tanA}$$ - $$\frac 1{{\frac 1{tan3A}} - {\frac 1{tanA}}}$$

=$$\frac 1{tan3A - tanA}$$ - $$\frac {\frac 1{tanA - tan3A}}{tan3A tanA}$$

=$$\frac 1{tan3A - tanA}$$ - $$\frac {tan 3A tanA}{tanA - tan3A}$$

= $$\frac 1{tan3A - tanA}$$ +$$\frac {tan 3A tanA}{tan3A - tanA}$$

= $$\frac {1 + tan 3A tanA}{tan3A - tanA}$$

= $$\frac {\frac 1{tan3A - tanA}}{1 + tan3A tanA}$$

= $$\frac 1{cot (3A - A)}$$

= $$\frac 1{cot2A}$$

= tan 2A

Hence, L.H.S. = R.H.S. proved

L.H.S.

=$$\frac {cos\theta}{cos\theta - sin\theta}$$ -$$\frac {cos\theta}{cos\theta +sin\theta}$$

= $$\frac {cos\theta (cos\theta + sin\theta) - cos\theta (cos\theta - sin\theta)}{(cos\theta - sin\theta) (cos\theta + sin\theta)}$$

= $$\frac {cos^2\theta + cos\theta sin\theta - cos^2\theta + cos\theta sin\theta}{cos^2\theta - sin^2\theta}$$

= $$\frac {2 sin\theta cos\theta}{cos^2\theta - sin^2\theta}$$

= $$\frac {sin 2\theta}{cos 2\theta}$$

= tan 2$$\theta$$

Hence, L.H.S. = R.H.S. Proved

L.H.S.

=$$\frac {1 - cos 2A + sin2A}{1 + cos 2A + sin2A}$$

= $$\frac {2sin^2A + 2sinAcosA}{2cos^2A + 2sinAcosA}$$ [$$\because$$ 1 - cos2A = 2sin2A and 1 + cos2A = 2cos2A]

= $$\frac {2sin A (sinA + cosA)}{2cosA (cosA + sinA)}$$

= tanA

Hence, L.H.S. = R.H.S. proved

L.H.S.

=$$\frac {1 - tan^2(\frac {π}{4} - \theta)}{1 + tan^2(\frac {π}{4} - \theta)}$$

= cos 2($$\frac {π}{4} - \theta)$$

= cos($$\frac {π}{2} - 2\theta)$$

= sin 2$$\theta$$

hence, L.H.S. = R.H.S. Proved

L.H.S.

=$$\frac {sin 3A}{sinA}$$ - $$\frac {cos 3A}{cosA}$$

= $$\frac {3 sinA - 4 sin^3A}{sinA}$$ - $$\frac {4 cos^3A - 3 cosA}{cosA}$$

= $$\frac {sinA (3 - 4 sin^2A)}{sinA}$$ - $$\frac {cosA (4 cos^2A - 3)}{cosA}$$

= 3 - 4 (1 - cos2A) - 4 cos2A + 3

= 3 - 4 + 4 cos2A - 4 cos2A + 3

= 6 - 4

= 2

Hence, L.H.S = R.H.S. Proved

L.H.S.

=4 cosec 2A . cot 2A

= 4($$\frac 1{sin2A})$$ . $$\frac {cos 2A}{sin 2A}$$

= $$\frac {4 (cos^2A - sin^2A)}{2 sinA cosA . 2 sinA cosA}$$

= $$\frac {cos^2A - sin^2A}{sin^2A cos^2A}$$

= $$\frac {cos^2A}{sin^2A cos^2A}$$ - $$\frac {sin^2A}{sin^2A cos^2A}$$

= $$\frac {1}{sin^2A}$$ - $$\frac {1}{cos^2A}$$

= cosec2A - sec2A

Hence, L.H.S. = R.H.S. proved

Here,

cosA = $$\frac {15}{17}$$

cosA

= $$\sqrt {1 - cos^2A}$$

= $$\sqrt {1 - (\frac {15}{17}})^2$$

= $$\sqrt {1 - \frac {225}{289}}$$

= $$\sqrt {\frac {289 - 225}{289}}$$

= $$\sqrt {\frac {64}{289}}$$

= $$\frac 8{17}$$

∴ tanA = $$\frac {sinA}{cosA}$$ = $$\frac {\frac {8}{17}}{\frac {15}{17}}$$ = $$\frac 8{15}$$

Now,

tan 3A

= $$\frac {3 tanA - tan^3A}{1 - 3 tan^2A}$$

= $$\frac {3 × \frac 8{15} - (\frac 8{15})^3}{1 - 3 ×(\frac 8{15})^2}$$

= $$\frac {\frac {24}{15} - \frac {512}{3375}}{1 - \frac {192}{225}}$$

= $$\frac {\frac {5400 - 512}{3375}}{\frac {225 - 192}{225}}$$

= $$\frac {\frac {4888}{3375}}{\frac {33}{225}}$$

= $$\frac {4888}{3375}$$× $$\frac {225}{33}$$

= $$\frac {4888}{15 × 33}$$

= $$\frac {4888}{495}$$ Ans

L.H.S.

=$$\frac 1{tan 3A + tanA}$$ - $$\frac 1{cot 3A + cotA}$$

= $$\frac 1{tan 3A + tanA}$$ - $$\frac 1{{\frac 1{tan 3A}} + {\frac 1{tanA}}}$$

= $$\frac 1{tan 3A + tanA}$$ - $$\frac {\frac 1{tanA + tan3A}}{tan3A tanA}$$

= $$\frac 1{tan 3A + tanA}$$ - $$\frac {tan 3A tanA}{tan 3A + tanA}$$

= $$\frac {1 - tan 3A tanA}{tan 3A + tanA}$$

= $$\frac {\frac 1{tan 3A + tanA}}{1 - tan3A tanA}$$

= $$\frac 1{tan (3A + A)}$$

= $$\frac 1{tan 4A}$$

= cot 4A

Hence, L.H.S. = R.H.S. Proved

L.H.S.

=$$\frac {1 + sin 2A}{cos 2A}$$

= $$\frac {sin^2A + cos^2A + 2 sinA cosA}{cos^2A - sin^2A}$$

= $$\frac {(cosA + sinA)^2}{(cosA + sinA) (cosA - sinA)}$$

= $$\frac {cosA + sinA}{cosA - sinA}$$

Hence, L.H.S. = R.H.S. Proved

Here,

sin 2$$\theta$$

= $$\frac {2 tan\theta}{1 + tan^2\theta}$$

= $$\frac {2 × \frac 43}{1 + (\frac 43)^2}$$

= $$\frac {\frac 83}{1 + \frac {16}{9}}$$

= $$\frac {\frac83}{\frac {9 + 16}{9}}$$

= $$\frac {\frac 83}{\frac {25}9}$$

= $$\frac 83$$× $$\frac 9{25}$$

= $$\frac {24}{25}$$ Ans

Here,

cos A = $$\frac 35$$

sinA

= $$\sqrt {1 - cos^2 A}$$

= $$\sqrt {1 - (\frac 35)^2}$$

= $$\sqrt {1 - \frac 9{25}}$$

= $$\sqrt {\frac {25 - 9}{25}}$$

= $$\sqrt {\frac {16}{25}}$$

= $$\frac 45$$

Now,

sin 2A

= 2 sinA cosA

= 2× $$\frac 45$$× $$\frac 35$$

= $$\frac {24}{25}$$ Ans

0%
• ### If sin A = (frac{3}{4}), find the value of cos 2A.

- (frac{8}{8})

- (frac{1}{-1})

- (frac{1}{8})

-(frac{1}{8})

• ### If 5sinθ = 4 , find the value of cos 2θ.

- (frac{8}{23})

(frac{-7}{15})

(frac{7}{25})

- (frac{7}{25})

• ### If cosθ = (frac{3}{4}) , find the value of sin 2θ

(frac{3 sqrt{16}}{7})

(frac{3 sqrt{7}}{8})

(frac{sqrt{5}}{2})

(frac{-3 sqrt{-7}}{-3})

• ### If cosθ = (frac{12}{13}) and sinα = (frac{4}{5}) , find the value f 2θ  and cos 2α .

(frac{100}{169}) , (frac{25}{-7})

(frac{120}{169}) , (frac{-7}{25})

(frac{10}{19}) , (frac{-25}{7})

(frac{220}{069}) , (frac{-7}{25})

• ### If cosθ = (frac{3}{5}) , find the value of cos 3θ .

(frac{-117}{125})

(frac{127}{150})

(frac{117}{-125})

(frac{125}{115})

• ### If cosθ = (frac{4}{5}) , find the value of cos3θ .

(frac{24}{144})

- (frac{44}{125})

- (frac{3}{15})

(frac{-44}{125})

• ### If sinα = (frac{3}{4}) , find the value f cos 2α and sinα .

(frac{8}{1}) , (frac{9}{16})

(frac{9}{8}) , (frac{19}{10})

(frac{-1}{-8}) , (frac{9}{-16})

- (frac{1}{8}) , (frac{9}{16})

• ### If tan (frac{A}{2}) = (frac{3}{4}) , find the numerical value of tan A.

(frac{24}{7})

(frac{-21}{7})

(frac{24}{6})

(frac{21}{3})

• ### If cos (frac{A}{2}) = (frac{3}{5}) , find the value of cos A.

- (frac{7}{21})

- (frac{7}{25})

(frac{17}{15})

(frac{-7}{-25})

• ### Find the value of sin 15(^o) if cos 30(^o) = (frac{sqrt{3}}{2}) .

(frac {sqrt{1-3} }{3 sqrt{1}})

(frac{sqrt{1-2}}{2 sqrt{0}})

(frac{sqrt{3-1}}{2 sqrt{2}})

(frac{sqrt{3+1}}{2 sqrt{-2}})

22

21

24

12

• ### Express sin A interms of cot (frac{A}{2}).

(frac {-2cotfrac A-2}{1 + cot^3frac A3})

(frac {1cotfrac A1}{3 + cot^-3frac- A2})

(frac {2cotfrac A2}{1 + cot^2frac A2})

(frac {2cotfrac A4}{3 + cot^2frac A1})

1

2

-1

-2

• ### If sin (frac{θ}{3}) = (frac{4}{5}) , find the value of sinθ.

(frac{144}{44})

(frac{30}{15})

(frac{125}{44})

(frac{44}{125})

2

1

-2

3

• ## You scored /15

Forum Time Replies Report